Common fixed points for (ψ,α,β)-weakly contractive mappings in generalized metric spaces - Işık, Hüseyin; Türkoğlu, Duran (Hindawi Publishing Corporation, 2013)
We establish some common fixed point theorems for mappings satisfying a (?, ?, ?)-weakly contractive condition in generalized metric spaces. Presented theorems extend and generalize many existing results in the literature. © 2013 Işik and Türko?lu; licensee Springer.
Keywords: Common fixed points; Contraction of integral type; Fixed point; Generalized metric; Weakly contractive condition